Role of university entrepreneurship programs in developing students' entrepreneurial leadership competencies : perspectives from Malaysian undergraduate students. - Bagheri, Afsaneh; Lope Pihie, Zaidatol Akmaliah (Taylor & Francis Group, 2013)
The authors aimed to identify the role of university entrepreneurship education programs in developing students’ entrepreneurial leadership competencies. A total of 18 interviews were conducted with students and university entrepreneurship program coordinators. From these, 16 prominent roles of the programs emerged and were classified into 2 clusters: student-related and program-related roles. Student-related roles reflect the contributions of the programs in developing personal and interpersonal leadership competencies of students. Program-related roles are the roles that the programs play in organizing and sustaining various entrepreneurial leadership learning opportunities, linking students to the world of entrepreneurial venturing, and having a holistic approach to university entrepreneurship programs.